Letramento crítico e o livro didático de inglês: uma análise dos textos e das atividades de compreensão escrita - Deize Costa Cardoso (2011)
This research investigated the promotion of critical literacy in an English textbook collection for the High School level. Based on the theories of critical literacy, expressed by OCEM (BRAZIL, 2006), which focuses on the educational, citizen and critical character of foreign language teaching, and on the principles of 'post-method condition', proposed by Kumaravadivelu (2003, 2006), this research aimed to understand whether the texts and the written comprehension activities, presented in the reading section of an English textbook collection for the High School level, contributed to the development of students critical literacy awareness . The qualitative methodology involved a documentary research as the investigation method. The analyses included an overview of the students book and the teacher's manual, a set of texts situated in the reading section, in terms of genre, support and authenticity, and the selection of six texts for a deeper analysis. The results of the analysis revealed the promotion of critical literacy is only related to the themes proposed in the texts but it is not a reality in reading activities as a whole yet. The results also showed the activities do not promote students critical positioning towards texts, and the theoretical and methodological bases in the teacher's manual are not sufficient neither for understanding the theory on which the didactic collection is based on nor for guiding a pedagogic practice in a more critical perspective.